Exploring fertility differentials between tea and ex-tea garden laborers of Assam - Kalita, Lipika; Choudhury, Hari K. (International Journal of Public Health Science (IJPHS), 2024)
Addressing the issue of high fertility rates among tea garden laborers in Assam is critical due to its adverse effects on the health of both mothers and children, diminished investment in human capital, stunted economic growth, and exacerbated environmental challenges. To effectively tackle this challenge, we need to delve into two key questions: What perpetuates high fertility rates, and how can we mitigate them? The solution lies in a comprehensive analysis of the immediate and underlying factors influencing fertility. Fertility is a multifaceted demographic phenomenon influenced by both direct and indirect determinants. In this study, we investigate the impact of various proximate and distant factors on fertility among two groups: The tea garden labor community in Assam and the ex-tea garden labor community, comprising individuals who have transitioned to other forms of employment. Our research identifies significant factors such as wife's age at marriage, breastfeeding duration, educational attainment, family size, duration of married life, child mortality, respondent category, and wife's occupational status that affect fertility levels in Assam's tea garden community. The study's findings indicate the need for implementing targeted family planning and reproductive health education programs within tea garden communities. These programs should offer comprehensive information and resources to assist individuals in making informed decisions regarding family size and reproductive health.